2019
DOI: 10.1371/journal.pone.0209223
|View full text |Cite
|
Sign up to set email alerts
|

Lithium is able to minimize olanzapine oxidative-inflammatory induction on macrophage cells

Abstract: BackgroundOlanzapine (OLZ) is a second-generation antipsychotic drug used for treatment of schizophrenia, bipolar disorder, and other neuropsychiatric conditions. Undesirable side effects of OLZ include metabolic alterations associated with chronic oxidative-inflammation events. It is possible that lithium (Li), a mood modulator that exhibits anti-inflammatory properties may attenuate OLZ-induced oxi-inflammatory effects.MethodologyTo test this hypothesis we activated RAW 264.7 immortalized macrophages with OL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Olanzapine is a second-generation antipsychotic drug with side effects, including metabolic alteration associated with low-grade systemic inflammation. The in vitro study by Fernandes et al [ 99 ] used the activated RAW 267.7 macrophages treated with OLZ or OLZ and lithium, and evaluated the oxidation and inflammation at the gene and protein expression level. The macrophages treated only with OLZ showed increased proliferation and higher levels of oxidative markers and pro-inflammatory cytokines, with reduced anti-inflammatory IL-10 level.…”
Section: Lithium Influences Inflammation and Energy Metabolismmentioning
confidence: 99%
“…Olanzapine is a second-generation antipsychotic drug with side effects, including metabolic alteration associated with low-grade systemic inflammation. The in vitro study by Fernandes et al [ 99 ] used the activated RAW 267.7 macrophages treated with OLZ or OLZ and lithium, and evaluated the oxidation and inflammation at the gene and protein expression level. The macrophages treated only with OLZ showed increased proliferation and higher levels of oxidative markers and pro-inflammatory cytokines, with reduced anti-inflammatory IL-10 level.…”
Section: Lithium Influences Inflammation and Energy Metabolismmentioning
confidence: 99%
“…The general protocols used here were similar to those previously described by Barbisan et al (2017), Duarte et al (2018), Fernandes et al (2019, involving in vitro psychotropic drug analysis on macrophage inflammatory response. As macrophages are highly sensitive to antigens and other antigenic factors, in the presence of these molecules, intense cellular proliferation and morphological changes occurs.…”
Section: General Experimental Designmentioning
confidence: 99%
“…These alterations, especially cellular proliferation in 72 h cell cultures, can be used as markers of the inflammatory activation of immune cells. The pro-inflammatory effects of OLZ at different concentrations were determined by Fernandes et al (2019). OLZ at a concentration 0.03 µg/mL was used in the experiments, since this represents the OLZ values expected to have a clinical effect and to be in the plasmatic therapeutic range of this drug.…”
Section: General Experimental Designmentioning
confidence: 99%
“…It has been suggested that iron could be associated with the production of reactive oxygen species as a consequence of olanzapine treatment, since this drug has been related to an increase in ROS and superoxide. 47 In terms of Fe-binding proteins transferrin is the main extracellular iron transport protein in blood that, when bound with iron, interacts with transferrin receptors to cause an internalization of that complex of iron and proteins into cells. Data on transferrin and transferrin receptor suggest a perturbation of iron uptake in subjects not only with major depressive disorder, but also with SCZ and BD.…”
Section: Metallobiomolecules Evaluationmentioning
confidence: 99%